DAKWAH DAN PERUBAHAN SOSIAL - Taufik Akhyar (Wardah, 2014)
Islam can not be separated by dakwah, adherents were also not able to separate dakwah from the practice of Islam itself. Qur'an as a way of life many revealing various aspects of human life by emphasizing the importance of social development, but Indonesia as a country with a Muslim majority in fact still experiencing a variety of social issues, such as poverty, ignorance, and a variety of helplessness in the field social, whereas the expression of wisdom explained that poverty is the infidelity. While proselytizing activities primarily conducted by the preacher continued, but the activity seems more likely to be rhetorical thus provide less especially in the field of social change. Therefore, the call must be understood correctly and wider covering all aspects of human life to realize that human beings have depressed individuals and social piety, thus dakwah can be one instrument for social change better